Optimalisasi Pendapatan Pengemudi Ojek Konvensional melalui Inovasi Layanan Prima dan Adaptasi Transaksi Digital di Persatuan Ojek Marelan - Dalim, Muhammad; Rangkuti, Agus Edi; Harahap, Irwan Musriza; Nasruddin; Suriyadi (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2025)
This Community Partnership Service Program (PKM) aims to increase the income of economically productive communities, specifically the Conventional Motorcycle Taxi Service Business, also known as the Marelan Motorcycle Taxi Association (POM). The Marelan Motorcycle Taxi Association is located at Simpang Pasar 1 Tanah Enam Ratus, Medan Marelan District, Medan City, North Sumatra Province. The problem faced by partners is the low daily income of their business members, which is around Rp. 30,000 - Rp. 50,000 per day per member. The cause of this problem is that partners do not understand how to promote their motorcycle taxi base to customers, partners do not understand how to provide good service (prime service) to their service users, partners do not have motorcycle taxi base identification attributes that are their characteristics, and the physical condition of the business location, such as tables and signboards, is too outdated. Through this Community Service program, a team from Medan State Polytechnic provides solutions in the form of promotion and prime service training, distributes ID jackets, creates new nameplates for the Motorcycle Taxi Association, and renovates tables and chairs at the Motorcycle Taxi Base Post. It is hoped that with the various solutions offered, the daily income of the Marelan Motorcycle Taxi Association (POM) partner members can increase.